Rose Red - Baxley, Craig R.; Phillips, Robert F.; Brodek, Thomas H.; King, Stephen, 1947-; Travis, Nancy, 1961-; Keeslar, Matt.; Brown, Kimberly J.; Dukes, David, 1945-2000.; Ivey, Judith, 1951-; Lynskey, Melanie; Ross, Matt.; Sands, Julian; et al. ([United States] : Trimark Home Video : Distributed by Lions Gate Home Entertainment, 2002)
The chilling tale of Dr. Joyce Reardon, an obsessed psychology professor who commissions a team of psychics and a gifted 15-year-old autistic girl, Annie, to literally wake up a supposedly dormant haunted mansion-- Rose Red. Their efforts unleash myriad spirits and uncover horrifying secrets of the generations who have lived and died there.
disc 1. Chapters 1-24 -- disc 2. Chapters 25-36 and special features.
Originally broadcast on television as a mini series in 2002.
Language options taken from DVD menu screen; all language options may not be present on container.
Special features: Production commentary; storyboard comparisons; Unlocking "Rose Red - the diary of Ellen Rimbauer"; The making of "Rose Red"; artwork gallery.
Director of photography, David Connell ; editor, Sonny Baskin ; music, Gary Chang ; costume designer, Ron Leamon ; production designer, Craig Stearns.
Nancy Travis, Matt Keeslar, Kimberly J. Brown, David Dukes, Judith Ivey, Melanie Lynskey, Matt Ross, Julian Sands, Kevin Tighe.
MPAA rating: PG-13; for terror/violence and sexual references.
Keywords: King, Stephen, -- 1947- -- Television adaptations; Haunted houses -- Washington (State) -- Seattle -- Drama; Autistic children -- Washington (State) -- Seattle -- Drama; Psychics -- Washington (State) -- Seattle -- Drama; Washington (State) -- Seattle; Television programs -- United States; Video recordings; Television adaptations; Drama; Feature films; Horror films; Video recordings for the hearing impaired